Can Temperament and Character Traits Be Used in the Diagnostic Differentiation of Children With ADHD?. Issue 12 (December 2021) - Ucuz, Ilknur; Uzun Cicek, Ayla; Cansel, Neslihan; Kilic, Bahar; Colak, Cemil; Percinel Yazici, Ipek; Kilic, Fatma; Kucukakcali, Zeynep
Abstract : Abstract: In this study, it was aimed to determine the contributions of temperament and character traits to the diagnosis of attention deficit hyperactivity disorder (ADHD) in children. Thirty-six patients between the ages of 9 and 14 with a diagnosis of combined type ADHD and 39 healthy children were included in the study. The Schedule for Affective Disorders and Schizophrenia for School-Age Children–Present and Lifetime Version–Turkish Version and the Turgay DSM-IV Disruptive Behavior Disorders Rating Scale parent form were used to assess hyperactivity/impulsivity and inattentiveness, and comorbid disorders. The Junior Temperament and Character Inventory–Revised form was used to evaluate temperament–character traits. The classification-based association rules (CBARs) method was used for finding rules predicting ADHD accurately. Low persistence and self-directedness scores, and higher disorderliness and fatigability subgroup scores were found in the ADHD group. In CBARs, the separation of children with ADHD from healthy controls could be made with 0.83 accuracy, 0.80 sensitivity, and 0.86 specificity. The results of our study support the view that temperament–character traits can help clinical diagnosis of ADHD.